2002
DOI: 10.1037/0882-7974.17.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapists' nonverbal communication predicts geriatric patients' health outcomes.

Abstract: Two studies explored the link between health care providers' patterns of nonverbal communication and therapeutic efficacy. In Study 1, physical therapists were videotaped during a session with a client. Brief samples of therapists' nonverbal behavior were rated by naive judges. Judges' ratings were then correlated with clients' physical, cognitive, and psychological functioning at admission, at discharge, and at 3 months following discharge. Therapists' distancing behavior was strongly correlated with short-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 69 publications
1
116
0
5
Order By: Relevance
“…shown to influence their behavior toward their client (e.g., Rosenthal, Blanck, & Vannicelli, 1984),which, in turn, may impact upon cognitive and functional outcomes for clients (e.g., Ambady, Koo, 1 Rosenthal, & Winograd, 2002). Given that therapists' other-efficacy beliefs were associated with 2 increases in their own relationship quality perceptions in this investigation (i.e., actor effect), it is 3 possible that this may have been reflected in the therapist engaging in more pro-social behavior 4 toward the client (e.g., support, encouragement, body language), leading to improvements in the 5 client's perceptions of relationship quality (see Snyder & Stukas, 1999).…”
Section: Results 23mentioning
confidence: 99%
“…shown to influence their behavior toward their client (e.g., Rosenthal, Blanck, & Vannicelli, 1984),which, in turn, may impact upon cognitive and functional outcomes for clients (e.g., Ambady, Koo, 1 Rosenthal, & Winograd, 2002). Given that therapists' other-efficacy beliefs were associated with 2 increases in their own relationship quality perceptions in this investigation (i.e., actor effect), it is 3 possible that this may have been reflected in the therapist engaging in more pro-social behavior 4 toward the client (e.g., support, encouragement, body language), leading to improvements in the 5 client's perceptions of relationship quality (see Snyder & Stukas, 1999).…”
Section: Results 23mentioning
confidence: 99%
“…Reverse causality is likely to be relevant for some variables, for example, psychosocial talk (which is likely to occur in consultations with more distress and emotion expressed) was associated with negative perception of communication. Although Rosenthal et al have shown that naïve raters can use their scales reliably, [21][22][23] judgements about each item will inevitably be subjective, although the impact of a single rater's judgement was minimised by using several raters. Similarly, despite using the Stewart method which has an extensive manual, 2 the estimation of reliability in this study suggests that for many variables reliability is only likely to be moderate, and so the associations may have been underestimated.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The literature shows a clear focus on the study of the verbal exchange during the medical visit [3,19]. However, considering nonverbal behavior in the medical conversation is important because nonverbal behavior is linked to patient satisfaction [20][21][22], patient compliance [23,24], and even patient health outcomes [19,[25][26][27]. In the present research we will thus consider not only verbal, but mostly nonverbal aspects of physician behavior: which verbal and nonverbal physician behaviors are related to the perception of the female and the male physician as dominant by the patient?…”
Section: Introductionmentioning
confidence: 99%